OVERVIEW OF LANGUAGE LEARNING IN SENSE RELATION: SAMENESS AND OPPOSITENESS - Yusuf Faidah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2018)
This article is about overview of language learning in sense relation. The aim of this article is to know sameness and oppositeness in sense relation of language learning. The method was based on library research. Study about language, so study about the meaning of that language because language is a tool of communication to each other. Semantic is study about the meaning, the meaning of a language could be seen from its relationship between words. The sense of one word is related to another sense. In this case, the result of this research is there are two main groups of sense relations. The first group is the sense relations with regard to the similarity or sameness (synonymy, hyponymy, entailment, paraphrase, metonymy, anaphora, presupposition). The second one is the sense relations of oppositeness (antonymy, anomaly, ambiguity, polysemy, homonymy, contradiction). Those are explained in this article.